2021
DOI: 10.18231/j.ijced.2021.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of Super bioavailable Itraconazole 50 mg in dermatophytosis (Clear 50)

Abstract: Super bioavailable itraconazole (SBITZ) is a newer formulation of itraconazole which is recently launched in India. But there is no published clinical evidence of SBITZ in the management of dermatophytosis in Indian patients. A Real world retrospective data analysis was conducted with 346 dermatologists across India to assess the response of Indian patients with dermatophytosis who were prescribed super bioavailable itraconazole 50 mg twice a day for 4 weeks.Out of 4625 patients’ data, 2743 were included for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
1
3
1
Order By: Relevance
“…The authors concluded that SB-Itraconazole is an effective alternate for new, chronic as well as recurrent cases of dermatophytosis. 18 However, we did not find any better clinical or mycological clearance with SB itraconazole as compared to conventional itraconazole. Limitation 1.…”
Section: Discussioncontrasting
confidence: 63%
“…The authors concluded that SB-Itraconazole is an effective alternate for new, chronic as well as recurrent cases of dermatophytosis. 18 However, we did not find any better clinical or mycological clearance with SB itraconazole as compared to conventional itraconazole. Limitation 1.…”
Section: Discussioncontrasting
confidence: 63%
“…While 78% of individuals in our study experienced a reduction in LSS, 93% of patients in the SB 50 group did so in a previously published study. 18 In our investigation, greater LSS clearance was seen with SB 65 group. Similar results were also found for ASS clearance demonstrating superiority of SB 65 over SB 50 group.…”
supporting
confidence: 48%
“…Dermatophytosis responds well to systemically administered ITZ [31]. Over the last decade, ITZ has emerged as the mainstay of systemic treatment for recalcitrant dermatophytosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data on the usage of SB ITZ in Indian patients are scarce. Different dosage forms are currently being marketed in the USA, Europe, and India [30,31]. This study aimed to reach a consensus on the suitability, dosage, duration of treatment, and advantages of SB ITZ in managing dermatophytosis in different clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation